ANALISIS EFISIENSI PENGGUNAAN MODAL PADA BALAI BENIH IKAN DI SULAWESI TENGGARA - Irdam Riani; Mirnawati Firdaus; Muis Balubi; Nurmut Mainah Nurmut Mainah; Yulita Chorolina Mangidi; Fadhilah Nur Hanifah; Muhammad Akbar; Awaluddin Awaluddin; Samsuddin Samsuddin (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2017)
Efficient use of capital is a major activity and a very important consideration taken into account in a business because it is very determining the size of the profits that can be obtained. The purpose of this study is to analyze the advantages and the level of efficiency of capital use on BBI Abeli Sawah Konawe district and BBI Ranomeeto South Konawe district. The research type is survey with quantitative approach which can explain the efficiency of cost utilization at BBI Abeli Sawah dan BBI Ranomeeto. The results showed that the average profit of BBI Abeli rice field was Rp 46,492,667, and BBI Ranomeeto was Rp44,030,667. Furthermore the efficiency level of capital use on BBI Abeli Sawah and BBI Ranoomeeto was still low, where each had value RC 1.24 and 1.19